Cilostazol-imprinted polymer film-coated electrode as an electrochemical chemosensor for selective determination of cilostazol and its active primary metabolite. Issue 35 (20th December 2021) - Jyoti,; Rybakiewicz-Sekita, Renata; Żołek, Teresa; Maciejewska, Dorota; Gilant, Edyta; Buś-Kwaśnik, Katarzyna; Kutner, Andrzej; Noworyta, Krzysztof R.; Kutner, Wlodzimierz
Abstract : An electrochemical chemosensor for cilostazol (CIL) determination was devised, engineered, and tested. Abstract : An electrochemical chemosensor for cilostazol (CIL) determination was devised, engineered, and tested. For that, a unique conducting film of the functionalized thiophene-appended carbazole-based polymer, molecularly imprinted with cilostazol (MIP-CIL), was potentiodynamically deposited on a Pt disk electrode by oxidative electropolymerization. Thanks to electro-oxidation potentials lower than that of CIL, the carbazole monomers outperformed pyrrole, thiophene, and phenol monomers, in this electropolymerization. The pre-polymerization complexes quantum-mechanical and molecular dynamics analysis allowed selecting the most appropriate monomer from the three thiophene-appended carbazoles examined. The electrode was then used as a selective CIL chemosensor in the linear dynamic concentration range of 50 to 924 nM with a high apparent imprinting factor, IF = 10.6. The MIP-CIL responded similarly to CIL and CIL's pharmacologically active primary metabolite, 3, 4-dehydrocilostazol (dhCIL), thus proving suitable for their determination together. Simulated models of the MIP cavities binding of the CIL, dhCIL, and interferences' molecules allowed predicting chemosensor selectivity. The MIP film sorption of CIL and dhCIL was examined using DPV by peak current data fitting with the Langmuir (L), Freundlich (F), and Langmuir–Freundlich (LF) isotherms. The LF isotherm best described this sorption with the sorption equilibrium constant ( K LF ) for CIL and dhCIL of 12.75 × 10 −6 and 0.23 × 10 −6 M, respectively. Moreover, the chemosensor cross-reactivity to common interferences study resulted in the selectivity to cholesterol and dehydroaripiprazole of 1.52 and 8.0, respectively. The chemosensor proved helpful in determining CIL and dhCIL in spiked human plasma with appreciable recovery (99.3–134.1%) and limit of detection (15 nM).